(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2014)
Abstrak Sewang merupakan salah satu komponen yang sangat penting dalam budaya masyarakat Orang Asli. Ia bukan sahaja sekadar bertujuan untuk keraian dan hiburan, malah lebih penting dari itu iaitu berperanan sebagai satu kaedah perubahan dan medium komunikasi antara manusia dengan makhluk halus, roh nenek moyang dan semangat yang mendiami alam ini. Berdasarkan bukti etnografi, sejarah dan survei yang dijalankan di Kampung Pasik, Hulu Kelantan, makalah ini akan membincangkan tentang aspekaspek yang terkandung dalam budaya sewang dan sejauhmanakah ia berperanan dalam masyarakat Orang Asli Temiar di Kampung Pasik, Hulu Kelantan ini. Abstract Sewang plays an important role in Orang Asli sosio-cultural life. It is not only regarded as one of their significance performing arts but also as an important medium of communication between human and spirits that inhabited this realm. Sewang is performed widely in the Orang Asli daily life and served as an important ritual practiced. Based on ethnographic evidence, history and surveys carried out in the Temiar settlements in Pasik, Hulu Kelantan, this paper will discuss to what extent sewang play its role in the Temiar’s society in terms of method, meaning and functions. It is hope that the discussion will give an insight of the significance role of sewang and enhance better understanding and awareness among us in order to sustained it as our cultural heritage.